2009
DOI: 10.1007/978-3-540-79090-7_10
|View full text |Cite
|
Sign up to set email alerts
|

Purines and Sensory Nerves

Abstract: P2X and P2Y nucleotide receptors are described on sensory neurons and their peripheral and central terminals in dorsal root, nodose, trigeminal, petrosal, retinal and enteric ganglia. Peripheral terminals are activated by ATP released from local cells by mechanical deformation, hypoxia or various local agents in the carotid body, lung, gut, bladder, inner ear, eye, nasal organ, taste buds, skin, muscle and joints mediating reflex responses and nociception. Purinergic receptors on fibres in the dorsal spinal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 245 publications
0
65
0
1
Order By: Relevance
“…Last years, a long series of discoveries has demonstrated that ATP is not only an energy currency inside cells, but it is also a critical signaling molecule that allows cells and tissues throughout the body to communicate with one another (32,33). This new aspect of ATP as an intercellular signaling molecule allows broadening the understanding of universality phenomenon of photosensitivity of cytochrome c oxidase.…”
Section: Irradiation In Visible-to Ir-a Region Causes Atp Extrasynthementioning
confidence: 99%
See 1 more Smart Citation
“…Last years, a long series of discoveries has demonstrated that ATP is not only an energy currency inside cells, but it is also a critical signaling molecule that allows cells and tissues throughout the body to communicate with one another (32,33). This new aspect of ATP as an intercellular signaling molecule allows broadening the understanding of universality phenomenon of photosensitivity of cytochrome c oxidase.…”
Section: Irradiation In Visible-to Ir-a Region Causes Atp Extrasynthementioning
confidence: 99%
“…The specific receptors for ATP as for the signaling molecule (P2 family) and for its final breakdown product, adenosine (P1 family), were found and identified (32,33). ATP activation of P2 receptors (subtypes P2X and P2Y) can produce different cellular effects.…”
Section: Irradiation In Visible-to Ir-a Region Causes Atp Extrasynthementioning
confidence: 99%
“…Messenger RNAs for P2Y 1,2,4,6,12,13,14 subtypes have been found in DRG neurons [30,31,32], suggesting that these receptors may play an ancillary role in peripheral somatosensory transmission [33,34]. P2Y receptors are located not only in the cell body, but also in peripheral and central terminals [35,36], where their activity is presumably integrated within the complex molecular network associated with the transmission of nociceptive signals to the CNS. Functional P2Y 1,2,4 receptors are also expressed in subsets of TG sensory neurons [30,37], but to date their role in the modulation of trigeminal pain has not been properly investigated.…”
Section: Modulation Of Pain Transmission By P2y Receptors In Sensory mentioning
confidence: 99%
“…ATP and nitrogen oxide are cotransmitters that interact with the classical neurotransmitters (acetylcholine, norepinephrine, dopamine). ATP and norepinephrine have been described in the postganglion of the vas deferens (Westfall et al, 2002;Burnstock, 2009) and are always coreleased.…”
Section: Discussionmentioning
confidence: 99%